Penerapan Mashlahah Mursalah Sebagai Pertimbangan Hakim Dalam Memutus Perkara di Pengadilan Agama - M Hasbi Umar; Muhammad Muhammad; Warfian Saputra (Wajah Hukum, 2020)
The use of mashlahah mursalah as a basis for legal determination among ulama is still disputed until it is divided into two groups, namely the group that uses mashlahah mursalah and the group that does not use mashlahah mursalah, but the difference of opinion has no effect on religious judges in Indonesia, because there are several decisions of religious judges. Applying mashlahah mursalah as a basis for consideration in his decision. This is as stated in the decision of the Jambi Religious Court judge in the Divorce Case Number 634 / Pdt.G / 2019 / PA.Jmb, Marriage Dispensation Number 40 / Pdt.P / 2020 / PA.Jmb, and Isbat Nikah Number 14 / Pdt. P / 2017 / PA.Jmb. This is based on several legal considerations, namely first, using mashlahah mursalah as argument and legal reasoning based on evidence and facts in court. Second, avoiding the harm that seekers of justice are facing with the aim of achieving the essence of sharia, namely protecting religion, soul, mind, descent and property.